Technologies in personnel recruiting Processes and personnel selection: academic production mapping - Gaspar, Denis Juliano; Schwartz, Gisele Maria (Revista Hipótese, 2018)
The technologies have been widely utilized by modern companies in Personnel Recruiting Processes and Personnel Selection, in order to bring agility and economy to people involved as well. Although these aspects, it is unknown the problems and concerns involving their effectiveness, as well as, its limitations and obstacle, which are necessary a closer appreciation. This qualitative nature study, was focused on the survey of academic studies approach the application of technologies in Personnel Recruitment and Selection Processes. The study was developed through systematic review associated with an exploratory research accomplished by periodicals website at CAPES/ MEC, also considering studies which tackle with specific themes of Recruitment and Personnel Selection and Technologies, focused on, recruitment team as well as selectors and selection processes participants. Data was descriptively analyzed by Content Analysis Technique. Results show a few academic production about the theme, even though they show positive aspects about technologies utilization in personnel recruitment and selection processes, some precaution is recommended, mainly about information exposure, and even, candidates image on the Internet. It is important to extend this scope about researches in order to support the selectors approach to candidates and their position in the market place.